Successful monotherapy of pemphigus vegetans with minocycline and nicotinamide. (7th September 2016) - von Köckritz, A.; Ständer, S.; Zeidler, C.; Metze, D.; Luger, T.; Bonsmann, G.
Abstract: Background: Pemphigus vegetans is a rare variant of pemphigus vulgaris, accounting for 1–2% of all pemphigus diseases. Systemic corticosteroids are the therapy of first choice in combination with immunosuppressants as steroid‐sparing agents. Objective: To highlight the exceptional but successful use of minocycline/nicotinamide monotherapy in pemphigus vegetans. Methods: A review of the literature to date about pemphigus vegetans with special emphasis on therapy was performed. Due to its rarity, multiple anecdotal reports without long‐term follow‐up are available and prospective controlled trials are lacking. Only one retrospective study from Tunisia includes 17 patients with pemphigus vegetans. Results: We present a 76‐year‐old woman with pemphigus vegetans achieving complete response to a minocycline/nicotinamide monotherapy at onset and at relapse of the disease. Treatment has been discontinued after repeated direct immunofluorescence (DIF) of previously affected normal skin and anti‐desmoglein 3 antibodies had become negative. In addition, DIF of previously involved oral mucosa was negative. During long‐term follow‐up clinical remission has been maintained for more than 5 years. Up to now, negative results of serial performed indirect immunofluorescence and desmoglein ELISA testing also predict immunological remission. Conclusion: In our patient and in a case with oesophageal involvement, published more than 20 years ago, clearly the benefit of minocycline/nicotinamide monotherapy was demonstrated. We propose to consider minocycline/nicotinamide as first‐line monotherapy in pemphigus vegetans, especially in elderly patients with comorbidities and contraindications to standard therapy, as it avoids the toxicities of systemic corticosteroids and immunosuppressants.